System-Wide Characterization of MoArf GTPase Family Proteins and Adaptor Protein MoGga1 Involved in the Development and Pathogenicity of Magnaporthe oryzae - Shengpei Zhang (American Society for Microbiology, 2019)
ABSTRACT ADP ribosylation factor (Arf) small GTPase family members are involved in vesicle trafficking and organelle maintenance in organisms ranging from Saccharomyces cerevisiae to humans. A previous study identified Magnaporthe oryzae Arf6 (MoArf6) as one of the Arf proteins that regulates growth and conidiation in the rice blast fungus M. oryzae, but the remaining family proteins remain unknown. Here, we identified six additional Arf proteins, including MoArf1, MoArl1, MoArl3, MoArl8, MoCin4, and MoSar1, as well as their sole adaptor protein, MoGga1, and determined their shared and specific functions. We showed that the majority of these proteins exhibit positive regulatory functions, most notably, in growth. Importantly, MoArl1, MoCin4, and MoGga1 are involved in pathogenicity through the regulation of host penetration and invasive hyphal growth. MoArl1 and MoCin4 also regulate normal vesicle trafficking, and MoCin4 further controls the formation of the biotrophic interfacial complex (BIC). Moreover, we showed that Golgi-cytoplasm cycling of MoArl1 is required for its function. Finally, we demonstrated that interactions between MoArf1 and MoArl1 with MoGga1 are important for Golgi localization and pathogenicity. Collectively, our findings revealed the shared and specific functions of Arf family members in M. oryzae and shed light on how these proteins function through conserved mechanisms to govern growth, transport, and virulence of the blast fungus. IMPORTANCE Magnaporthe oryzae is the causal agent of rice blast, representing the most devastating diseases of rice worldwide, which results in losses of amounts of rice that could feed more than 60 million people each year. Arf (ADP ribosylation factor) small GTPase family proteins are involved in vesicle trafficking and organelle maintenance in eukaryotic cells. To investigate the function of Arf family proteins in M. oryzae, we systematically characterized all seven Arf proteins and found that they have shared and specific functions in governing the growth, development, and pathogenicity of the blast fungus. We have also identified the pathogenicity-related protein MoGga1 as the common adaptor of MoArf1 and MoArl1. Our findings are important because they provide the first comprehensive characterization of the Arf GTPase family proteins and their adaptor protein MoGga1 functioning in a plant-pathogenic fungus, which could help to reveal new fungicide targets to control this devastating disease.